Selective enforcement and international criminal law: the International Criminal Court and Africa - Nyawo, James (Supranational criminal law, 2017)
Introduction -- The establishment of the International Criminal Court, and Africa's role and early support -- The office of the prosecutor and the politics of selecting tragets for prosecution -- State party referrals, Un Secutiry council referrals and the selection of situations -- Assessing selective enforcement from an admissibiity perspective -- The AU and African states' shift for cooperation to non-cooperation with the court -- African States' reaction to the AU's call for non-cooperation with the court -- Africa and the International Criminal Court ; the lessons and prospects